Performance of lithium polymer battery on electric propulsion system - Ahmad Fathi, Mohd Zainuddin (2013)
In recent years, most of the micro size UAVs are equipped with an electric propulsion system to reduce noise and thermal signatures. In some application the vehicle can be reused to perform subsequent mission due to endurance limitation and type of operation. In practice new battery system will be installed to reduce the risk of failures during operation. The present study is to determine the performance of Lithium Polymer battery. It shows that the new battery the internal resistance depending on manufacturer models and battery capacity.